Socio-economic impacts of major sports events. An analysis of the 2019 alpine and biathlon World Championships in Sweden - Wallstam, M.; Kronenberg, K.; Pettersson, R. (ETOUR, Part of Mid Sweden University, 2019)
In the winter of 2019, two major sports events took place in Jämtland county, Sweden. The events in question were the Alpine World Championships in Åre, and the Biathlon World Championships in Östersund. The proximity of the events in space and time garnered considerable attention both nationally and internationally. Moreover, a number of projects were initiated in the region in order to create synergies between the events and maximize the potential benefits from them. Amongst these initiatives was the creation of the World Championships Region 2019 (WCR 2019) network. The network is a joint project by the two organizing committees and was designed to spread the positive impacts of the events, both in terms of business networking and brand exposure for all forms of businesses, but also as a part of a wider push to attract new county residents. At the time of writing the network partners have decided to extend the project beyond its initial end point in order to continue to further build on the long-term legacy of the two events. As with most bid-based sports events, there was widespread interest in the returns that the region and its stakeholders would enjoy as a result of hosting them. Similarly, concerns were raised about the potential risks of hosting such large-scale events so close in time. There is still a lot to learn about planned events as it, along with tourism in general, is a relatively economic new sector in the world economy. However, mounting evidence has suggested that they should be treated with caution. Particularly in the case of mega-events such as Olympic Games or Football World Cups. Major sports events, such as the Alpine and Biathlon World Championships, have enjoyed relative anonymity in the presence of their Mega counterparts. In the case of these events, one could argue that the worldwide demand is more limited than that of the globally popular mega-events. However, there is an unquestionable potential for major events of this sort to incur significant impacts on regions and the local communities that constitute them. In light of the two events taking place, and the need to scrutinize such events, this report aims to provide some insight on their impacts.